Evaluation of progesterone receptor expression in low- and high-grade astrocytomas - Tavares,Cléciton Braga (2021)
SUMMARY OBJECTIVE: Gliomas are tumors originating from glial cells. Gliomas are the most common primary neoplasms of the central nervous system, with astrocytomas being the most prevalent glioma subtype. Progesterone regulates several reproductive processes, such as ovulation and sexual behavior, and influences neuronal excitability, learning, and the neoplastic proliferation of glial cells. Progesterone functions mainly by interacting with intracellular progesterone receptors to modify the expression of the genes involved in cell proliferation, angiogenesis, and epidermal growth factor production. As not many studies on the hormone receptors in glial tumors have been reported, the objective of this study was to evaluate the expression of these proteins in astrocytomas and to determine whether their expression levels vary according to the tumor grade. METHODS: This was a retrospective study using glial tumor paraffin blocks obtained from the São Marcos Hospital Pathology Department archives. Forty cases were divided equally into two groups, based on histological types and the World Health Organization criteria (low- and high-grade tumors). Progesterone receptor expression was analyzed by immunohistochemistry. The data were statistically analyzed using the Mann-Whitney U test and Spearman's correlation coefficient; results with p<0.05 were considered statistically significant. RESULTS: There were no statistically significant differences between the mean nuclear progesterone receptor expression of low-grade (0.1495) and high-grade (0.0937) astrocytomas (p=0.2). CONCLUSION: Progesterone receptors are present in both low- and high-grade gliomas; however, there is no significant difference in the levels of progesterone receptor expression between the tumor grades.